THE IMPACT OF ISLAMIC FINANCIAL ENGINEERING ON RISK MANAGEMENT IN ISLAMIC BANKS FOR A SAMPLE OF GULF BANKS - Sundus Jassim Shaaibith (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Engineering Finance field Take advantage in it Knowledge And competencies Areas Other Most importantly Mathematics And economy And information To study the information in a way Scientific Deep help On Take Decisions Investment Without Adventure And exposure For risks Fluctuations Markets Stock Exchange .Islamic banks have incorporated this concept into banking risk management while ensuring that Be Products Islamic Assent Of Islam The largest Saucepan Maybe, And This It includes Stay away Exit From Controversy Fiqh Saucepan As possible . As Not Target Basis From Industry Finance Islamic Weighting Opinion He is a priest On else, And But Reach to me Solution Innovative Be Shop an agreement Saucepan Possible . And on him Should that We will not beginning between Circle What he is permissible Sharia, And between What Aspiring mechanism Industry Islamic . The industry Islamic Aspiring For products And Mechanisms Typical that Right Expression . While Circle The project Include What may is being Typically Scale age The present, And What Not As well . Reason that Shara came For everyone in a Each Zaman, And Circumstances Individuals And Communities Vary And Vary.